The origin and properties of higher-order near- and far-field modes in plasmonic metal nano-rods - Hüseyin U. Tepe (Scientific Reports)
Abstract A hydrodynamic model within the discontinuous Galerkin method is used to simulate the non-linear optical properties of plasmonic gold nanorods. Highly pure spherical and vector spherical harmonics are obtained in the near and far-fields, where each over-tone and polarization represents a unique state. The nano-rods may be treated as switchable quasi-atoms, where the activating mechanism is the intense incident pulse. These properties might become useful in future quantum or optical computation applications. The pure harmonical states are explained by the localized Fermi gas pressure gradients, which is the main force driving the second harmonic generation (SHG).